(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the significance of pragmatics in discourse analysis, emphasizing how contextual factors, speech acts, and implicatures shape meaning. By examining existing literature, the study highlights the interplay between linguistic structure and social context. The findings underscore the necessity of pragmatic awareness in achieving effective communication and offer suggestions for future research.